FEATURES OF SACRED OBJECTS ALLOCATION WITHIN PODOLIA - ATAMAN , Lyudmyla (Ekonomichna ta Sotsialna Geografiya, 2014)
The article briefly and concisely defined and described the most interesting sacred objects of Podolia, peculiarities of their distribution. The basic elements of the territorial structure of sacred objects within Podolia. Among the objects of pilgrimage Vinnytsia region selected those which are most important in the development of the tourism industry in the region.

В статті коротко і стисло визначено й описано найбільш цікаві сакральні об’єкти Поділля, визначено особливості їх розміщення. Виділено основні елементи територіальної структури сакральних об’єктів Поділля. Серед об’єктів паломництва Вінницької області виділено ті, які мають найбільше значення у розвитку туристичної галузі регіону.
ОСОБЛИВОСТІ РОЗМІЩЕННЯ САКРАЛЬНИХ ОБ’ЄКТІВ ПОДІЛЛЯ
Keywords: sacred object; territorial organization; religious sphere; сакральний об’єкт; територіальна організація; релігійна сфера